Workshop On Making Biscuits Made From Banana Peel Flour (Musa Paradisiaca L): Workshop Pembuatan Biskuit Berbahan Dasar Tepung Kulit Pisang (Musa Paradisiaca L) - Nurjaya Nurjaya; Elvyrah Faisal; Indri Selfiani (Jurnal Pengabdian Masyarakat: Svasta Harena, 2022)
Indonesia is rich in abundant and diverse local food sources that have the potential to be developed. Various ways to support the national food security program are carried out to maximize the production and consumption of local food sources of non-rice and non-wheat carbohydrates, which are the government's priorities, especially in the field of diversification. The utilization of banana peels can be used as flour which can be made in various processed cakes such as biscuits. The nutritional content of kepok banana peel flour per 100 grams of material is 69.8 g of water, 18.50 g of carbohydrates, 0.32 g of protein, 2.11 g of fat, 715 g of calcium, 117 mg of phosphorus, 1.6 mg of iron, vitamins B 0.12 mg, vitamin C 17.5 mg. This of course can help meet the fiber needs needed by humans. The purpose of this activity is the utilization of banana peel waste to support food security programs. The activity was carried out by providing counseling on food security and demonstrations of making biscuits made from banana peels. This community service increases knowledge in utilizing banana peel waste by being able to make snacks that have nutritional value and can reduce organic waste. It is hoped that biscuits made from banana peel flour can become a favorite snack that is not less competitive and can open up insights for household-scale food production with banana peel raw materials.